Integrated Islamic Philanthropy for Equitable Healthcare Access: A Case Study of Muhammadiyah Hospital - Janah, Unun Roudlotul; Prasetiyo, Luhur (ZISWAF, 2025)
This study examines the integration of Islamic philanthropy within hospital settings, with a particular focus on Muhammadiyah Hospital in Ponorogo, Indonesia, to strengthen access to affordable healthcare for marginalized communities. The research is motivated by the limited scholarly attention to the incorporation of ZISWAF and corporate social responsibility (CSR) mechanisms in healthcare service practices, which represents a significant gap in contemporary Islamic philanthropy literature. Employing a qualitative research design, data were collected through interviews with philanthropic unit managers, hospital administrators, and beneficiaries of philanthropic programs. The findings reveal that Islamic philanthropy is integrated through a synergistic governance model that optimizes ZISWAF funds. Zakat and infaq are utilized to cover essential healthcare costs, with infaq serving as a complementary source when zakat eligibility criteria do not apply. Meanwhile, waqf contributes to the procurement of fixed assets, including buildings and patient facilities. The integrated philanthropic unit within the hospital functions as a consolidating entity for managing ZISWAF funds. This integration substantially enhances healthcare accessibility for underserved populations. The study contributes to the literature by conceptualizing an Islamic philanthropic integration model for hospital contexts and proposing the inclusion of CSR as an additional funding stream supporting healthcare-based philanthropic initiatives.